1983
DOI: 10.1002/ajpa.1330600409
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal growth in a medieval population from Sudanese Nubia

Abstract: Long bone growth is analyzed for 180 children from a Medieval population at Kulubnarti in Sudanese Nubia (550–1450 A.D.). A regional interpopulation comparison is made with growth data from Wadi Halfa in Lower Nubia, and an intrapopulation analysis is undertaken to assess diachronic changes in growth at Kulubnarti. Changes in growth patterns are interpreted in the context of mortality and morbidity profiles and relationships between the three variables are discussed. It is suggested that changes in the sociopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
2

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 11 publications
2
46
1
2
Order By: Relevance
“…The geographical, ecological, and archaeological contexts of the site have been well described elsewhere (Hummert, 1983a,b; Hummert and Van Gerven, 1983;Van Gerven et al, 1981).…”
Section: Methodsmentioning
confidence: 98%
“…The geographical, ecological, and archaeological contexts of the site have been well described elsewhere (Hummert, 1983a,b; Hummert and Van Gerven, 1983;Van Gerven et al, 1981).…”
Section: Methodsmentioning
confidence: 98%
“…Concerning growth disruption, comparative studies have repeatedly demonstrated that the growth of long bone length is a sensitive indicator of environmental stress (e.g. Johnston, 1962;Hummert and Van Gerven, 1983;Jantz and Owsley, 1984;Mensforth, 1985;Lovejoy et al, 1990), although this index probably has limited application due to methodological problems that have not yet been fully resolved (Johnston and Zimmer, 1989;Saunders, 1992). The most serious problem arises in relation to variation among the methodologies of estimating age.…”
Section: Environmental Stress Based On Growth Disruption Of Femur Lengthmentioning
confidence: 99%
“…Johnston, 1962;Hummert and Van Gerven, 1983;Jantz and Owsley, 1984;Mensforth, 1985;Lovejoy et al, 1990). Moreover, subadult remains can contribute to the clarification of the causation of morphological differences observed among adult skeletons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these cemetery samples show evidence for developmental and childhood stress as reflected in high incidences of cribra orbitalia, retarded long bone growth velocities, and substantial infant and juvenile mortality (Van Gerven et al, 1981;Hummert and Van Gerven, 1983). If there is a relationship between developmental stress and fluctuating asymmetry in the dentition, as has been suggested (Perzigian, 1977;Doyle and Johnston, 19771, then it would seem ,likely that the Kulubnarti archeological populations should show some degree of fluctuating asymmetry.…”
Section: Methodsmentioning
confidence: 90%